DEVELOPMENT MODULE ACCOUNTING FOR IMPROVING THE INDEPENDENCE AND LEARNING STUDENT ACHIEVEMENT STUDENTS THE CLASS XII SMAN KOTA BENGKULU - Rosdiana Rosdiana; Johanes Sapri; Bambang Sahono (UNIB Press, 2017)
This research purpose to increase the independence and student achievement in the class X students majoring in accounting at SMA N 5 Bengkulu through the development modul of teaching materials of introductory finance and accounting. This research is the development of the subject of the research that teachers and students are in class XII IPS 1 to 20 students, of 35 students the class XII IPS 2 and 2 teacher introduction to the financial and accounting, while the object of this research is the module material introductory teaching finance and accounting. Analysis techniques by observation, interviews, expert judgment, questionnaires, research documentation and test results of learning. Based on these results it can be concluded that the development of teaching materials introductory finance and accounting module can increase the independence and student achievement.Keywords: module accounting, independence, learning achievement